Effectiveness of a Didactic and Practical Oral Health Education Program among Primary School Children - F Eslamipour; I Asgari (Isfahan University of Medical Sciences, 2007)
Introduction: The aim of this study was evaluation of the effectiveness of a didactic and practical oral health education program for improving oral health knowledge among primary school children. Methods and Materials: The participants were 560 children, 9-11 years-old, selected from different geographic areas of Isfahan with stratified random sampling method. This oral health education project consisted of one classroom-based lesson with hands on training reinforced by practical session for tooth brushing and flossing. A validated and reliable questionnaire was used to demonstrate children's oral health knowledge prior, just after, one week, and two months after following the program (Chronbahch alpha = 0.74).The collected data were analyzed on SPSS software with repeated measurement ANOVA and cochrane statistical tests.Results: The mean grade of the knowledge from the maximum of 100 was 45 ± 16.7 prior to the intervention. Following the program this grade increased to 78± 20.2 which showed a significant improvement in oral health knowledge (p value < 0.001). One week and two months after program the mean grade of knowledge was 78 ± 19 and 79 ± 17.7 respectively. No significant loss of knowledge was detected (p value = 0.36).Conclusion: Based on this study, the oral health education program implemented in Isfahan community dentistry center, improved the level of knowledge in this age group. Moreover, its efficacy to produce a stable increase in oral health knowledge was shown.Key word: Dental health education, health knowledge, primary school children